Wastewater Treatment - Ince, Muharrem; Kaplan Ince, Olcay (IntechOpen, 2022)
This book focuses on advances in monitoring and controlling wastewater treatment processes using recent technologies. It also discusses new and groundbreaking developments in the field of organic-inorganic pollution. As a comprehensive book, it takes a broad view of the subject and integrates a wide variety of approaches. Written by leading experts in their fields, this book is highly recommended for readers and scholars interested in environmental and human health.